The protective effect of IL‐12/23 neutralizing antibody in sarcopenia associated with dextran sulfate sodium‐induced experimental colitis. Issue 2 (5th March 2023) - Jung, Youn‐Kwan; Lee, Sangyeob; Yoo, Jun‐Il; Baek, Kyung‐Wan
Abstract: Background: The improvement of colitis symptoms by treatment with IL‐12/23 p40 neutralizing antibody should increase the muscle mass and the function of the sarcopenia phenotype. Methods: An experimental colitis model was induced by oral administration of 2% dextran sulfate sodium (DSS) for 7 days. During induction of colitis, IL‐12/23 p40 neutralizing antibody was injected twice on Days 3 and 5. The total body mass index was measured by dual‐energy X‐ray absorptiometry. The muscle function was measured by forelimb grip strength and fatigue running distance. The muscle fibre cross‐sectional area (CSA) was calculated after the transverse section and haematoxylin and eosin staining, and gene expression was confirmed by RT‐qPCR. Differentiated C2C12 cells were used as in vitro models and treated with recombinant IL12/23 proteins to mimic the enhanced cytokines in colitis. Results: The symptoms of colitis were alleviated by injection of IL‐12/23 p40 neutralizing antibody compared with phosphate‐buffered saline (PBS), and the disease activity index score was significantly lower on Day 8 (0.0 ± 0.00 of cont. vs. 11.3 ± 0.9 of DSS + PBS, P  < 0.0001; DSS + PBS vs. 7.7 ± 1.25 of DSS + p40Ab, P  < 0.0001). The CSA of the gastrocnemius and tibialis anterior muscle fibres decreased in mice with DSS‐induced colitis (gastrocnemius, 1258.2 μm 2 ± 176.45 of cont. vs. 640.1 μm 2 ± 59.83 of DSS + PBS, P < 0.0001; tibialis anterior, 1251.8 μm 2 ± 331.48 of cont. vs. 678.9 μm 2 ± 67.59 of DSS + PBS, P < 0.0001), and the treatment of IL‐12/23 p40 neutralizing antibody partially restored CSA of the gastrocnemius (640.1 μm 2 ± 59.83 of DSS + PBS vs. 1062.0 μm 2 ± 83.41 of DSS + p40Ab, P < 0.0001) and tibialis anterior (678.9 μm 2 ± 67.59 of DSS + PBS vs. 1105.3 μm 2 ± 143.15 of DSS + p40Ab, P = 0.0003).vs. 640.1 μm 2  ± 59.83 of DSS + PBS, P  < 0.0001) and tibialis anterior (1251.8 μm 2  ± 331.48 of cont. vs. 678.9 μm 2  ± 67.59 of DSS + PBS, P  < 0.0001), and the treatment of IL‐12/23 p40 neutralizing antibody partially restored CSA of the gastrocnemius (640.1 μm 2  ± 59.83 of DSS + PBS vs. 1062.0 μm 2  ± 83.41 of DSS + p40Ab, P  < 0.0001) and tibialis anterior (678.9 μm 2  ± 67.59 of DSS + PBS vs. 1105.3 μm 2  ± 143.15 of DSS + p40Ab, P  = 0.0003). In the evaluation of muscle function, grip strength and fatigue distance decreased by colitis were partially restored (grip strength: 139.9 g ± 5.38 of cont. vs. 83.9 g ± 5.48 of DSS + PBS, P  < 0.0001; DSS + PBS vs. 118.6 g ± 4.05 of DSS + p40Ab, P  < 0.0001; fatigue distance: 872.5 m ± 104.01 of cont. vs. 58.2 m ± 107.72 of DSS + PBS, P  < 0.0001; DSS + PBS vs. 328.0 m ± 109.71 of DSS + p40Ab, P  = 0.0015) by injection of IL‐12/23 p40 neutralizing antibody. Conclusions: Our study demonstrates that Il‐12/23 acts directly on muscle to induce atrophy, and the IL‐12/23 p40 neutralizing antibody is effective not only in suppressing colitis but also in maintaining muscle mass and improving muscle function in an experimental colitis model.